International Rainwater Catchment Systems Experiences Towards sustainability - Gleason Espíndola, José Arturo; Casiano Flores, César Augusto (IWA Publishing, 2020)
Harvesting rain and using it for drinking and domestic use will help to give scattered rural households and under-served city dwellers access to water. The world cannot ignore using rain - as the source of all water. This book presents stories and experiences from some 15 countries from all over the globe, developed and less developed. There are many more experiences that can be highlighted, but those included are thought to give the reader a good overview of what can be done when water supply engineering investment has not yet reached the unserved. Rainwater harvesting has an important role to play as a safe water supply when other sources are not safe or not available. A rainwater system brings along storage. It may be perceived as a little expensive but will normally be cheaper than a house connection from a centrally treated water supply system. Moreover, the storage will be invaluable in an emergency when tankered water can be stored. Also, in times of drought households with rainwater storage will still have a supply of water.